Assessment and management of adult ankle fractures: understanding the evidence. (2nd May 2021) - Yip, Grace; Hay, Daniel; Stringfellow, Tom; Ahluwalia, Aashish; Ahluwalia, Raju
Abstract : Ankle fractures are a common injury. Assessment should include looking at the mechanism of injury, comorbidities, associated injuries, soft tissue status and neurovascular status. Emergent reduction is required for clinically deformed ankles. Investigations should include plain radiographs and a computed tomography scan for more complex injuries or those with posterior malleolus involvement. An assessment of ankle stability determines treatment, taking into account comorbidities and preoperative mobility which need special consideration. Non-operative management includes splint or cast, allowing for early weightbearing when the ankle is stable. Operative management includes open reduction and internal fixation, intramedullary nailing (of the fibula and hindfoot) and external fixation. Syndemosis stabilisation includes suture button or screw fixation. The aim of treatment is to restore ankle stability and this article explores the current evidence in best practice.